Ministry to the sick and dying in the late medieval church - Izbicki, Thomas M. (The Catholic University of America Press, 2023)
"The focus of this volume is on ministry to the sick and dying in the later Middle Ages, especially providing them with the sacraments. Medieval writers linked illness to sin and its forgiveness. The priest, as physician of souls, was expected to heal the soul, preparing it for the hereafter. His ministry might also effect healing of bodies, when that healing did not endanger the soul. This book treats how a priest prepared to visit sick persons and went to them in procession with the Eucharist and oil of the sick. The priest was to comfort the patient and, if death was imminent, prepare the soul for the hereafter. Canon law, theology, and ritual sources are employed. Three sacraments, penance, viaticum, (final communion) and extreme unction (anointing of the sick) are treated in detail. Sickbed confession was designed to forgive the ailing person's mortal sins. A priest could absolve a dying person of all sins, even those reserved to a bishop or the pope. Viaticum was to strengthen a suffering Christian for life's last conflict, that between angels and demons for the soul of the dying person. The deathbed thus was a spiritual battlefield. Extreme unction was reserved for those in danger of death, relieving the soul of venial sins or "the remains of sin," even after confession and absolution. The commendatio animae (commendation of the soul) used with the dying was to usher the soul into the afterlife. Many works have been written about attitudes toward death, dying, and the afterlife in the Middle Ages. Likewise, there is a good deal of literature about individual sacraments. This study aims at bridging between these literatures, with a focus on the priest and parishioner in both theory and practice at the sickbed"--